LEVEL OF THE GUALITY OF LIFE OF THE PATIENTS AFTER ESOPHAGOPLASTY ON THE BASIS OF GASTROINTESTINAL INDEX ASSESSMENT - I. E. Sudovykh; E. A. Drobyazgin; Yu. V. Chikinev (Вестник хирургии имени И.И. Грекова)
The article presents the interview results of 55 patients after esophagoplasty (30 cases - after esophagogastroplasty, 25 cases - after esophagoplasty) using questionnaire GIQLI. The authors came to conclusions about advantages of extirpation of esophagus with esopagogastroplasty compared with subtotal shunt esophagocoloplasty because of high rate of gastrointestinal index of the quality of life and their components in patients after esophagogastroplasty compared with results of patients after esophagoplasty. There was noted an expessed growth in the scales and rise of gastrointestinal index in patients who underwent esophagogastroplasty after 3 years of follow-up.